An assessment of the knowledge management readiness of the benefits and gratuity claims unit of the AFP pension and gratuity management center with implications of implementing a knowledge management initiative - Agcaoili, Andrea Jessica E. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
The AFPPGMC, specifically the Benefits and Gratuity Claims Unit, handles hundreds of benefit claims cases every day. All sorts of documents and pertinent information are submitted to the unit and this can become overwhelming to manage. The BGCU administration may not be privy to the benefits of applying KM initiatives into their day to day processes because of gaps in the practices associated with managing knowledge assets.